Web 2.0 the global SOA. - Hinchcliffe, Dion
The subject of Web 2.0 has become profoundly important over the last year. Web 2.0 describes the next generation of the Web as an application platform where most of a user's software experience resides. The subject is somewhat controversial, but it's becoming ever more apparent as the successor to monolithic system architecture, prepackaged software and traditional Web applications.